The Place of Religious Law in Western Societies - Rohe, Mathias (World Scientific Publishing Co., 2022)
The following sections are included: Introduction Regulations on the Relations between the State and Religions in Europe The Application of Religious Norms under European Legal Orders The Application of Islamic Legal Norms in Europe References
CRIS-Team Scopus Importer:2024-06-28